1998
DOI: 10.1143/jpsj.67.1118
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Local Density of States ofdx2-y2-Wave Superconducting State Near the Surfaces of thet-JModel

Abstract: Spatial dependencies of the pair potential and the local density of states near the surfaces of d x 2 −y 2 -wave superconductors are studied theoretically. The calculation is based on the t-J model within a mean-field theory with Gutzwiller approximation. Various types of surface geometries are considered. Similar to our result in the extended Hubbard model, it is found that the formation of zero-energy states strongly depends on the surface geometry. In addition to this feature, the zero-energy states give pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
3

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 29 publications
3
42
3
Order By: Relevance
“…That is, the measurement of the conductance in ab-plane tunneling experiments can give information on the presence of a surface order parameter in HTS that spontaneously breaks time reversal symmetry. Recently, this effect has been found to be consistent with the t − J-model [61] in the case of sufficiently large J at the surface of a d-wave superconductor [62,63].…”
Section: Splitting Of the Zero Bias Conductance Peak By A Broken Timesupporting
confidence: 52%
“…That is, the measurement of the conductance in ab-plane tunneling experiments can give information on the presence of a surface order parameter in HTS that spontaneously breaks time reversal symmetry. Recently, this effect has been found to be consistent with the t − J-model [61] in the case of sufficiently large J at the surface of a d-wave superconductor [62,63].…”
Section: Splitting Of the Zero Bias Conductance Peak By A Broken Timesupporting
confidence: 52%
“…The renormalized mean field Hamiltonian can then be written as [83], . The self-consistent determination of order parameters within the renormalized Bogoliubov-de Gennes theory was also applied to study surface effects in 2D superconducting states [144,145].…”
Section: Applications To Inhomogeneous Systemsmentioning
confidence: 99%
“…As regards the roughness of the surface, we believe it is necessary to study tunneling spectroscopy of κ-(BEDT-TTF) 2 Cu(NCS) 2 in the presence of atomic scale roughness as done by Tanuma et al on a lattice model. 21,22 As for the issue of random scattering effect by impurities, Asano et al 37 have shown, both from analytical and numerical calculation beyond quasiclassical approximations, that impurity scattering near the interface in the high-T C cuprates can induce a splitting or a disappearance of the ZBCP. From this viewpoint, it would also be interesting to study the impurity scattering effect in κ-(BEDT-TTF) 2 Cu(NCS) 2 .…”
Section: Discussionmentioning
confidence: 99%